Visuality, photography, and media in international relations theory: A review - Kirkpatrick, Erika (Media, war & conflict, 2015)
The way we see war – its visuality – is ever changing and dynamic. Despite the theoretical variety in International Relations (IR) scholarship, the themes of visuality, photography, and media have not been considered in a systematic fashion. The positivist core of IR is limited in its capacity to consider these themes outside of a cause-and-effect framework. This results in media mainly discussed in terms of its influence on international politics via its impact on (primarily American) foreign policy. The media and foreign policy literature follows this legacy; it arose as a response to post Cold War events and technological shifts. Similarly, the Revolution in Military Affairs of the 1990s opened up a space for strategic studies to address media and visuality. Recent literature from strategic studies engages with cultural and social theory in a way that shows how such tools may be used for exploitation as well as emancipation. In opposition, the post-positivist research tradition of critical IR theory problematizes the world created by rationalist–objectivist social science and seeks answers to constitutive questions about the construction, production, and performance of actors and structures in International Politics. Flowing from this, the visual securitization program rejects the rationalism of the media and foreign policy literature, while still investigating the links between media and decision-makers. Overall, critical IR theory has carved a productive space for dealing with these themes by breaking away completely from the rationalist legacy and putting forward a more hermeneutic – as opposed to positivistic – approach to the subject. This review concludes that the way IR has so far dealt with these themes narrows our field of vision and prevents us from envisioning the broader regime of representation of war photography, a claim to be upheld in future research.